2010
DOI: 10.1186/1471-230x-10-92
|View full text |Cite
|
Sign up to set email alerts
|

Infection with HIV and HCV enhances the release of fatty acid synthase into circulation: evidence for a novel indicator of viral infection

Abstract: BackgroundFatty acid synthase (FASN) is an enzyme synthesized by the liver and plays an important role in lipogenesis. The present study aimed to investigate whether serum FASN concentration may provide a direct link between HIV and/or HCV viral infections and lipid metabolic disorders commonly observed in HIV/HCV-infected patients.MethodsWe evaluated serum FASN concentration in 191 consecutive HIV-infected patients in the absence or presence of HCV co-infection. For comparison, 102 uninfected controls were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 36 publications
(43 reference statements)
0
20
0
Order By: Relevance
“…FASN expression is significantly increased in HCV-infected livers (37), and serum FASN concentrations are significantly increased in patients with chronic HCV infection (38,39). FASN is also upregulated in HCV-infected Huh7 cells (18).…”
Section: Discussionmentioning
confidence: 87%
“…FASN expression is significantly increased in HCV-infected livers (37), and serum FASN concentrations are significantly increased in patients with chronic HCV infection (38,39). FASN is also upregulated in HCV-infected Huh7 cells (18).…”
Section: Discussionmentioning
confidence: 87%
“…11,12 It has been previously demonstrated in vitro that FASN is upregulated in cells infected with HIV, HCV and HBV, 5,6,13 and we have recently proposed that the release of FASN into circulation is a novel indicator of viral infection in humans. 4 We have found in this study that serum FASN shows a significant predictive value for liver steatosis, and may segregate patients with different degree of steatosis. Such effects are not independent of increased serum ALT.…”
Section: Discussionmentioning
confidence: 93%
“…3 More recently, we have found that serum FASN concentration is significantly increased in HIV-infected individuals, and that the release of FASN into the circulation is further enhanced in patients who are co-infected with HCV. 4 However, we did not find any association with metabolic stress. Furthermore, it has been demonstrated in vitro that FASN is up-regulated during hepatitis C virus (HCV) infection and regulates HCV entry and production.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Fatty acid synthase (FASN) is a key lipogenic enzyme involved in fatty acids synthesis (Table 1; Figure 1A). Indeed, FASN protein levels are increased in HCV-infected patients [20,21] or HCV-infected cells [22,23]. Notably, Nasheri et al found that HCV NS4B was involved in FASN induction and concomitant increase in fatty acids production [23].…”
Section: Fatty Acids and Virus Genome Replicationmentioning
confidence: 99%